Glucocorticoid Treatment Strategies in Liver Failure - Ye, Chao; Li, Wenyuan; Li, Lei; Zhang, Kaiguang (Frontiers in Immunology, 2022)
Liver failure is characterized by serious liver decompensation and high mortality. The activation of systemic immune responses and systemic inflammation are widely accepted as the core pathogenesis of liver failure. Glucocorticoids (GCs) are most regularly utilized to suppress excessive inflammatory reactions and immunological responses. GCs have been used in the clinical treatment of liver failure for nearly 60 years. While there has been no unanimity on the feasibility and application of GC treatment in liver failure until recently. The most recent trials have produced conflicting results when it comes to the dose and time for GC therapy of different etiology of liver failure. Our review outlines the issues and options in managing GC treatment in liver failure based on an investigation of the molecular mechanism that GC may give in the treatment.